KONSTRUKSI MAKNA TARI PERSEMBAHAN OLEH PENARI PADA SANGGAR TARI DI LINGKUNGAN UNIVERSITAS RIAU - Ridho, Muhammad; Yohana, Nova (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
In consideration of the importance of Persembahan Dance as the identity of the culture, in 2009, Malay Customs Institution of Riau (LAMR) standardized this Persembahan Dance. This situation is done in consideration of that dance is getting difference and its disorder in terms of the form and the pattern which comes out of Malay mores.The type of this research was descriptive, was that qualitative study with phenomenological approach. The facts of the field study were gathered by doing observation and deep-interview documentation. The subjects of the research were the dancers of Riau University. This research was focused on the exploration of informant experience. The research questions of this research were (1) What is the motif of the dancer in Riau University in performing the Malay dance? (2) How do the dancers in Riau University elucidate the Persembahan Dance? (3) How the communicational experience of the dancer in Riau University in performing Persembahan Dance?The result of this research showed that the motif of the dancer in Riau University consisted of (because motive) those were pleasure feeling, experience, easy to be learnt, the meaning itself and the place whereas the (in order to motive) is that preserving the dance. The naming that given by the dancer in Riau University toward Persembahan Dance that they learned as an art creation, cultural preservation legacy, official welcoming guest and fee giver while the communicational experience was categorized as two experiences those were the pleasurable and displeasuring experience.Keyword: Construction Meaning, Persembahan Dance, Dancer Of Riau University Area.